Spatial Mapping of Infectious Diseases Cases for Puskesmas Surveillance Officers in the Work Area of the Depok City Health Office - Saputra, Rahmat; Devita, Yeni; Maemun, Siti; Fitri, Rahmi Pramulia; Zakiah, Zakiah (The Indonesian Journal of Infectious Diseases, 2025)
Background: Reflecting on the previous Covid-19 pandemic obtained from the results of the situation analysis, the author concludes that the  Depok City Health Office must be able to conduct data analysis spatially, thus causing a lack of information about the spread of cases based on specific places such as villages and  coordinate points (GPS), this data is useful for measuring how much disease spreads in an area and can support policy making and intervention quickly and appropriately. In addition, unlucky spa data is also useful for seeing the density of vectors in an area. Methods: The research method was Quasi Experimental using the One Group Pre-Test and Post-Test research design, with  a sample size of 40 people. The data collection technique uses pre-test and post-test questions,  spatial mapping practice exercises and  data  analysis and interpretation exercises. The training will be held from 19 to 20 November 2021 at the Depok City Health Office hall. The data analysis test used the Paired T-Test, because the data was not normally distributed, it was continued using Wilcoxon analysis. Results: The results of the study obtained a Z value of -5.581 with an Asymp value. Sig. (2-tailed) by 0.000. Because this value is < alpha (0.05), it can be concluded that there is a significant increase in knowledge by 5.6 times after receiving training. Conclusion: To improve the performance of officers in terms of spatial mapping of infectious diseases, it is expected to conduct evaluations every 3-6 months and transfer knowledge from old officers to new officers if there is a change of officers